'Socialist Accounting' by Karl Polanyi: with preface 'Socialism and the embedded economy' - Bockman, Johanna; Fischer, Ariane; Woodruff, David (Theory & Society, 2016)
Ariane Fischer, David Woodruff, and Johanna Bockman have translated Karl Polanyi's 'Sozialistische Rechnungslegung' ['Socialist Accounting'] from 1922. In this article, Polanyi laid out his model of a future socialism, a world in which the economy is subordinated to society. Polanyi described the nature of this society and a kind of socialism that he would remain committed to his entire life. Accompanying the translation is the preface titled 'Socialism and the embedded economy.' In the preface, Bockman explains the historical context of the article and its significance to the socialist calculation debate, the social sciences, and socialism more broadly. Based on her reading of the accounting and society that Polanyi offers here, Bockman argues that scholars have too narrowly used Polanyi's work to support the Keynesian welfare state to the exclusion of other institutions, have too broadly used his work to study social institutions indiscriminately, and have not recognized that his work shares fundamental commonalities with and often unacknowledged distinctions from neoclassical economics.
Sociology; Political Science
Keywords: Keynesian economics; Keynesianism; embeddedness; neoclassical economics; social accounting; socialism; socialist accounting; socialist calculation debate; welfare state